2005
DOI: 10.3748/wjg.v11.i15.2283
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression during capillary morphogenesis in a microcarrier-based three-dimensionalin vitromodel of angiogenesis with focus on chemokines and chemokine receptors

Abstract: The present study demonstrates a global profile of gene expression during endothelial capillary morphogenesis, and the results provide us much information about the molecular mechanisms of angiogenesis, with which further evaluation of individual genes can be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…A RayBio Human cytokine/growth factor antibody array identified several elevated factors in the supernatant, including inflammatory mediators with demonstrated roles in migration of mononuclear cells: IL-1h, Il-6, IL-8, IL-10, GRO, MCP-1, MIP1h, and RANTES [28,29]. Inflammation precedes angiogenesis, and several of the elevated cytokines from the CD133 À fraction (IL-8, GRO, MCP-1 and RANTES) have been implicated in regulating angiogenesis [30,31]. Studies have previously demonstrated interaction of progenitor cells and other sub-populations from the peripheral blood through cytokines, including the secretion of IL-8 and MCP-1 from CD14 + cells [15,32].…”
Section: Discussionmentioning
confidence: 99%
“…A RayBio Human cytokine/growth factor antibody array identified several elevated factors in the supernatant, including inflammatory mediators with demonstrated roles in migration of mononuclear cells: IL-1h, Il-6, IL-8, IL-10, GRO, MCP-1, MIP1h, and RANTES [28,29]. Inflammation precedes angiogenesis, and several of the elevated cytokines from the CD133 À fraction (IL-8, GRO, MCP-1 and RANTES) have been implicated in regulating angiogenesis [30,31]. Studies have previously demonstrated interaction of progenitor cells and other sub-populations from the peripheral blood through cytokines, including the secretion of IL-8 and MCP-1 from CD14 + cells [15,32].…”
Section: Discussionmentioning
confidence: 99%
“…extent of vascularization was dependent on survivin expression, since survivin-deficient mice had a significant reduction in blood vessel density. Recent microarray studies have identified numerous novel genes associated with the proliferative, adhesive and remodelling phases of angiogenesis ( [78,79]; for reviews, see [80,81]). …”
Section: Figure 4 Potential Pathways Of Angiogenesis and Ec Apoptosismentioning
confidence: 99%
“…Thus far a number of studies have been conducted that address the question, which genes are involved in capillary formation. Previous studies on gene profiling of angiogenic endothelium have focused on the isolation of endothelium from purely angiogenic and purely non-angiogenic conditions, such as EC embedded in collagen [6][7][8] or fibrin [9,10] matrices, or EC grown on matrigel [11]; EC isolated from tumor versus normal tissue [12,13]; or EC that had been stimulated with angiogenic factors with non-stimulated EC [14]. However, a comparison of gene expressions by tubule-forming and nontubule-forming endothelial cells that were both exposed to the same stimuli is still lacking.…”
Section: Introductionmentioning
confidence: 99%